Can the Testing Effect for General Knowledge Facts Be Influenced by Distraction due to Divided Attention or Experimentally Induced Anxious Mood? - Tse, Chi-Shing; Chan, Meingold Hiu-Ming; Tse, Wai-Shing; Wong, Savio Wai-Ho (Frontiers in Psychology, 2019)
Studies on testing effect have showed that a practice test on study materials leads to better performance in a final test than restudying the materials for the same amount of time. Two experiments were conducted to test how distraction, as triggered by divided attention or experimentally-induced anxious mood in the practice phase, could modulate the benefit of testing (vs. restudying) on the learning of interesting and boring general knowledge facts. Two individual difference factors (trait test anxiety and working memory capacity) were measured. Under divided attention, participants restudied or recalled the missing information in visually-presented general knowledge facts, while judging whether auditorily-presented items were from a pre-specified category. To experimentally induce anxious mood, we instructed participants to view and interpret negative pictures with anxious music background before and during the practice phase. Immediate and two-day delayed tests were given. Regardless of item type (interesting or boring) or retention interval, the testing effect was not significantly affected by divided (vs. full) attention or anxious (vs. neutral) mood. These results remained unchanged after taking into account the influences of participants’ trait test anxiety and working memory capacity. However, when analyses were restricted to the study materials that had been learnt in the divided attention condition while participants accurately responded to the concurrent distracting task, the testing effect was stronger in the divided attention condition than in the full attention condition. Contrary to previous studies (e.g., Tse & Pu, 2012), there was no working memory capacity × trait test anxiety interaction in the overall testing effect. Theoretical and practical implications of these findings are discussed.